Integrasi Gamifikasi pada Pembelajaran Berbasis Deep Learning di Sekolah Dasar - Rahmawati, Emma (Tarunateach: Journal of Elementary School, 2025)
This study explores the integration of gamification in the implementation of deep learning-based instruction in elementary schools. Deep learning is not a new curriculum, but rather a pedagogical approach that emphasizes meaningful, mindful, and joyful learning. The main objective of this study is to analyze how elements of gamification align with the principles of deep learning and how their implementation can enhance students’ conceptual understanding, reflective engagement, and learning motivation. The research employs a qualitative method using content analysis based on the Miles and Huberman model. Data were obtained from various literature sources, including scholarly journals, reference books, policy reports, and best practices in the field of education. The findings indicate that the integration of gamification supports deep learning, particularly when it is designed to connect learning materials with real-life contexts (meaningful), engage students in reflection and responsibility for their learning (mindful), and foster an interactive and enjoyable learning atmosphere (joyful). Furthermore, the study reveals that this approach aligns with the development of foundational literacy, 21st-century competencies, and adaptive character traits essential for learners in the digital era. Therefore, gamification can serve as an effective pedagogical strategy to promote the transformation of elementary education based on deep learning.